An application of SaTScan to evaluate the spatial distribution of corner kick goals in major league soccer - Schmicker, R. H. (International Journal of Computer Science in Sport, 2013)
Identifying strategy that helps increase the number of goals in soccer is paramount to success. Opportunities exist to increase success in set pieces such as free kicks and corner kicks. We examined all corner kicks attempted during the 2010 Major League Soccer season to assess whether goals scored off of corner kicks were randomly spatially distributed. We separated the 18-yard box into 66, three by four yard boxes. A spatial scan statistic implemented in SaTScan, varied at-risk percentages to assess areas with higher than expected rates of goals scored. We examined data from 1859 corner kicks with an overall goal rate of 2.2%. A single box directly in the center of the box, 6-9 yards from goal was the only box with significantly higher rates of goals scored (5.0%) than expected. This result did not vary after adjusting for potential confounders` home field, kick trajectory or time of game. Our results, which consider goal rates, are consistent with previous research that suggest the most aggregate goals are scored in an area 6-12 yards from goal. Future research is needed to account for player movement on corner kick attempts.